2011
DOI: 10.1375/twin.14.2.198
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Delivery of a Twin Pregnancy and Uterine Atony: Morphological and Clinical Evidence

Abstract: In the last ten years, there has been a significant increase in the number of twin pregnancies, particularly in relation to the increased use of assisted reproductive technologies. Concomitantly, the incidence of abortions or of premature births has also increased (Tummers et al., 2003). In the literature, there are reports of twin pregnancies, wherein there is the possibility for expulsion of the first fetus with subsequent continuation of the pregnancy and a positive outcome for the remaining fetus (Wouters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Furthermore, some studies have reported cases of pregnancy prolongation of more than 100 days. 8,[10][11][12] Delay of delivery beyond 36 weeks seems relatively scarce, and our case is an additional one.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, some studies have reported cases of pregnancy prolongation of more than 100 days. 8,[10][11][12] Delay of delivery beyond 36 weeks seems relatively scarce, and our case is an additional one.…”
Section: Discussionmentioning
confidence: 75%
“…The case with the longest interval between the births of both twins spanned 154 days. 8 Aydin and Celiloglu 9 described a case wherein, after the delivery of the first twin at 21 weeks' gestation, a 3639g infant was delivered with cesarean section at 36 weeks' gestation and had an uneventful neonatal course. Furthermore, some studies have reported cases of pregnancy prolongation of more than 100 days.…”
Section: Discussionmentioning
confidence: 99%
“…dIscusIón En 1879, Carson JCL reportó el primer caso de PA, con un intervalo de tiempo entre ambos partos de 44 días (4) . El PA con el intervalo más largo ha sido de 154 días (5) . Lamentablemente, no se conoce la incidencia real, ya que la bibliografía se limita a reportes de casos y series sujetas al sesgo de informar solo los resultados positivos.…”
Section: Reporte De Casounclassified
“…El riesgo de complicaciones maternas puede ser hasta de 38%, siendo las infecciones locales y sepsis las más frecuentes, seguidas por hemorragias posparto, desprendimientos de placenta, histerectomías posparto y fístulas uterovaginales. No se ha comunicado casos de muerte materna (2,5) . Asimismo, un estudio retrospectivo en pacientes con complicaciones graves describió amniocentesis negativas al evaluar la corioamnionitis subclínica, por lo que es importante resaltar que el riesgo podría ser difícil de predecir (11) .…”
Section: Reporte De Casounclassified
“…Since then, medical teams across the word have understood the considerable interest in delaying delivery of the remaining multiples after immature delivery. Countless case reports have been published, describing the feasibility of delaying the delivery of twins, triplets or higher-order multiples, the longest delay ever reached being 154 days [2].…”
Section: Introductionmentioning
confidence: 99%